Pelanggaran prinsip kesantunan dalam film Lara Ati serta implikasinya terhadap penonton - Hidayanti, Fitri (Magister Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2022)
Regional languages ​​do need to be preserved, but if in a general or national context, regional languages ​​must be set aside so as not to cause misunderstandings between speakers and speech partners. That is the case in the film Lara Ati by Bayu Skak which is September 2022. In this film 90% uses the regional language, namely Javanese, and several of the dialogues that are spoken are a violation of the principle of courtesy which has implications for the audience. In this study, researchers used a qualitative descriptive method with note-taking techniques. From the results of the study, six violations of the principle of politeness were obtained, including three violations of the maxim of sympathy, two violations of the maxim of wisdom, and one violation of the maxim of humility. The implication of violating the principle of courtesy is that the audience will be carried away and compelled to use speech or dialogue which turns out to contain a violation of the principle of courtesy.